3x*4(x+10)=620

Simple and best practice solution for 3x*4(x+10)=620 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x*4(x+10)=620 equation:


Simplifying
3x * 4(x + 10) = 620

Reorder the terms:
3x * 4(10 + x) = 620

Reorder the terms for easier multiplication:
3 * 4x(10 + x) = 620

Multiply 3 * 4
12x(10 + x) = 620
(10 * 12x + x * 12x) = 620
(120x + 12x2) = 620

Solving
120x + 12x2 = 620

Solving for variable 'x'.

Reorder the terms:
-620 + 120x + 12x2 = 620 + -620

Combine like terms: 620 + -620 = 0
-620 + 120x + 12x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-155 + 30x + 3x2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-155 + 30x + 3x2)' equal to zero and attempt to solve: Simplifying -155 + 30x + 3x2 = 0 Solving -155 + 30x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -51.66666667 + 10x + x2 = 0 Move the constant term to the right: Add '51.66666667' to each side of the equation. -51.66666667 + 10x + 51.66666667 + x2 = 0 + 51.66666667 Reorder the terms: -51.66666667 + 51.66666667 + 10x + x2 = 0 + 51.66666667 Combine like terms: -51.66666667 + 51.66666667 = 0.00000000 0.00000000 + 10x + x2 = 0 + 51.66666667 10x + x2 = 0 + 51.66666667 Combine like terms: 0 + 51.66666667 = 51.66666667 10x + x2 = 51.66666667 The x term is 10x. Take half its coefficient (5). Square it (25) and add it to both sides. Add '25' to each side of the equation. 10x + 25 + x2 = 51.66666667 + 25 Reorder the terms: 25 + 10x + x2 = 51.66666667 + 25 Combine like terms: 51.66666667 + 25 = 76.66666667 25 + 10x + x2 = 76.66666667 Factor a perfect square on the left side: (x + 5)(x + 5) = 76.66666667 Calculate the square root of the right side: 8.755950358 Break this problem into two subproblems by setting (x + 5) equal to 8.755950358 and -8.755950358.

Subproblem 1

x + 5 = 8.755950358 Simplifying x + 5 = 8.755950358 Reorder the terms: 5 + x = 8.755950358 Solving 5 + x = 8.755950358 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 8.755950358 + -5 Combine like terms: 5 + -5 = 0 0 + x = 8.755950358 + -5 x = 8.755950358 + -5 Combine like terms: 8.755950358 + -5 = 3.755950358 x = 3.755950358 Simplifying x = 3.755950358

Subproblem 2

x + 5 = -8.755950358 Simplifying x + 5 = -8.755950358 Reorder the terms: 5 + x = -8.755950358 Solving 5 + x = -8.755950358 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = -8.755950358 + -5 Combine like terms: 5 + -5 = 0 0 + x = -8.755950358 + -5 x = -8.755950358 + -5 Combine like terms: -8.755950358 + -5 = -13.755950358 x = -13.755950358 Simplifying x = -13.755950358

Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.755950358, -13.755950358}

Solution

x = {3.755950358, -13.755950358}

See similar equations:

| 6x+11=-43-8x | | 3x-7=28-4x | | y=6-5x-3x^2 | | 7+4x=-1+x | | x^3=2.5 | | 4u^2-5u-1=0 | | X/6=10/8 | | Cosx=sin(x+30) | | (2x-15)=(x+5) | | x*2+14x-20=0 | | X*x+X-6=y | | X*x+6-6=y | | 60+60*0+11= | | 3x^2=12x+15 | | z^3+3z+1=0 | | 8x+5+4x-5+x=180 | | 7y+4x=7 | | -23x+27=42x+19 | | 19x+42=18x | | 2px^2-6px+4p=0 | | 5x+42=32 | | 42/28/21 | | 5=8sin(1.06t) | | (46+y)+56+31=180 | | 0.3x+0.6y=15 | | z^2=-5-2i | | -x-3x+7=0 | | 18x+27=14x | | -32a^2-44a+15=0 | | 50x-5=14 | | x^4+6x^3+8x^2+6x+-9=0 | | (32-x)+x+(19-x)+4=50 |

Equations solver categories